Hybrid ferrocene-based systems - Kelly, M (2014)
This thesis explores the capacity of sterically and electronically unsaturated boranes to bind substrates of biological and environmental interest, and transduce such binding events into a photo-physical and/or electrochemical response, hence reporting the presence of these substrates. Chapter three details the synthesis of a range of novel ferrocenyl boranes featuring either a proximal hydrogen-bond donor or a second Lewis acidic centre. These novel boranes were shown to be competent at binding both cyanide and fluoride anions, with the role played by a proximal hydrogen-bond donor or a second Lewis acidic centre in anion binding investigated by both NMR and crystallographic studies. Chapter four reports the synthesis of novel pyridinyl and related boronic esters, as well as unexpected mixed alkenyl/aryl boranes. The capacity of both types of system to bind fluoride or cyanide anions in solution was investigated by UV-Vis and NMR studies. The photo-physical responses to these anions were also probed, leading to the establishment of both switch-on and switch-off fluorescent responses. Chapter five extends the knowledge derived from selective anion receptor design and combines this with recent developments in the field of frustrated Lewis pairs (FLPs) to activate, bind and report the presence of nitrous oxide (N2O) molecule. Thus, the syntheses of novel, highly Lewis acidic ferrocenyl boranes that incorporate a high degree of steric loading around the boron centre are reported. The electrochemical and photo-physical response of an FLP system to the presence of N2O was investigated leading to the development of a novel N2O reporting system.